2009
DOI: 10.1038/nprot.2009.194
|View full text |Cite
|
Sign up to set email alerts
|

Global identification of protein kinase substrates by protein microarray analysis

Abstract: SUMMARY We describe a protocol for the global identification of the in vitro substrates targeted by protein kinases using protein microarray technology. Large numbers of fusion proteins TAP-tagged at their carboxy-termini are purified in 96-well format and spotted in duplicate onto amino-silane coated slides in a spatially addressable manner. These arrays are incubated in the presence of purified kinase and radiolabeled ATP, and then washed, dried, and analyzed by autoradiography. The extent of phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 26 publications
(8 reference statements)
1
65
0
Order By: Relevance
“…Purified recombinant yeast proteins were printed on the nitrocellulose coated glass slides as previously described (13). Each microarray contains 4,800 fulllength GST fusion proteins spotted in duplicate (14,15).…”
Section: Protein Microarray Screen and Data Analysismentioning
confidence: 99%
“…Purified recombinant yeast proteins were printed on the nitrocellulose coated glass slides as previously described (13). Each microarray contains 4,800 fulllength GST fusion proteins spotted in duplicate (14,15).…”
Section: Protein Microarray Screen and Data Analysismentioning
confidence: 99%
“…Early studies in yeast were mostly aimed at identifying kinase substrates using in vitro kinase assays (6), whereas recent technological advances have enabled proteome-wide mapping of phosphorylation sites in vivo (7). Systems-level studies monitoring growth (1,8) or changes in the abundance of transcripts (9) or protein phosphorylation (7) in yeast have resolved the effect of deletion or overexpression of individual members of a network of greater than 130 kinases and 50 phosphatases.…”
Section: Introductionmentioning
confidence: 99%
“…Protease C and protein A Cterminal fusion tags were removed through the use of sitedirected ligase independent mutagenesis (SLIM) as described by Chiu et al [36] using the primers shown in Table S-1. The plasmids were then transformed into wildtype yeast cells using the LiAc method [37] and proteins were overexpressed as described by Gelperin et al [38] and Mok et al [39]. Five mL of cells were harvested, resuspended in 1 mL of induction media and methylated in vivo by incubating in 50 μM SAM for 90 min.…”
Section: Overexpression and In Vivo Methylation Of Npl3mentioning
confidence: 99%